Gender bias in evaluating assistant professorship applicants? Evidence from harmonized survey experiments in Germany and Italy - Klarita Gërxhani; Nevena Kulic; Alessandra Rusconi; Heike Solga (Social Science Research, 2025)
This study investigates gender biases in the evaluation of applicants for assistant professorships in Germany and Italy. Drawing on the justification-suppression model of prejudice expression, we explore whether biases against women are expressed, suppressed, or even reversed in the appointment process, considering the different normative gender climates and gender equality strategies in the two countries. Using harmonized factorial survey experiments with professors of economics, political science, and social sciences, we found that women in Germany have an advantage both in perceived qualification for an assistant professorship and in the propensity to receive an interview invitation. In contrast, women in Italy are neither disadvantaged nor advantaged. We also examine whether gender biases exist when there is ambiguity about applicants' academic performance (co-authorship) and career commitment (parental leave). Our results reveal a co-authorship penalty and a parenthood premium in both countries, with no gender differences observed. Our exploratory country comparison suggests that Germany's proactive gender equality policies may be more effective in reducing the gender gap in assistant professor appointments compared to Italy's gender-neutral approach, by favoring equally qualified female applicants.
Keywords: 300; Gender inequality; Academia; Standardization; Gender preferential selection; Vignette study